The evolution of regional planning and regional economic development in Malaysia - Rebe, Noor Suzilawati; Mohamed Osman, Mariana; Bachok, Syahriah (AWG Publishing Toronto Canada, 2013)
This article explains the evolution of regional planning and policy in Malaysia and discusses the implications of the underlying regional economic theories and regional policies for the socio-economic development of Malaysia. Regional economic development in Malaysia is due to several factors, including the integration of geography and physical features, the need for cooperation beyond local jurisdictions, and the needs of local and national economic development. A review of the literature suggests that the achievement and development of regional planning would differ depending on the country’s pattern of development and growth. However, the basis of regional planning remains the same: to promote competitiveness, create economic opportunities, and achieve balance in the socio-economic development of a country. In a way, regional planning is a tool to achieve sustainable development in a country